Maternal circulating GPIHBP1 levels and neonatal outcomes in patients with gestational diabetes mellitus: a pilot study - Watanabe, Mayu; Eguchi, Jun; Kurooka, Naoko; Eto, Eriko; Masuyama, Hisashi; Wada, Jun (Frontiers in Clinical Diabetes and Healthcare, 2025)
IntroductionThe prevalence of gestational diabetes mellitus (GDM) is significantly increasing. Hyperglycaemia and dyslipidaemia have been demonstrated to contribute to endothelial dysfunction linked to foetal–placental circulation. Glycosylphosphatidylinositol-anchored high-density lipoprotein-binding protein 1 (GPIHBP1) is crucial for the lipolytic processing of TG-rich lipoproteins through the anchoring of lipoprotein lipase (LPL). In this study, circulating GPIHBP1 levels during pregnancy were evaluated, and their associations with hypertriglyceridaemia and the perinatal outcomes of GDM were evaluated.MethodsThis study included 12 pregnant women with GDM and 21 pregnant women with normal glucose tolerance (NGT).ResultsNo significant differences in obstetrical outcomes were detected between the two groups. In participants with NGT, circulating GPIHBP1 levels were markedly lower in the 3rd trimester than in the 2nd trimester and at delivery. In women with GDM, circulating GPIHBP1 levels were unchanged during the 3rd trimester, and circulating GPIHBP1 levels throughout the 3rd trimester were negatively correlated with neonatal birth weight percentile and umbilical venous pO2 (ρ=-0.636, p=0.026; ρ=-0.657, p=0.020).DiscussionOur findings suggest a possible association between circulating GPIHBP1 levels and perinatal outcomes in patients with GDM.